2021
DOI: 10.1007/s10877-021-00764-3
|View full text |Cite
|
Sign up to set email alerts
|

Mathematically arterialised venous blood is a stable representation of patient acid–base status at steady state following acute transient changes in ventilation

Abstract: Hyper- or hypoventilation are commonly occurring stress responses to arterial puncture around the time of blood sampling and have been shown to rapidly alter arterial blood acid–base parameters. This study aimed to evaluate a physiology-based mathematical method to transform peripheral venous blood acid–base values into mathematically arterialised equivalents following acute, transient changes in ventilation. Data from thirty patients scheduled for elective surgery were analysed using the physiology-based meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Data are lacking on the prevalence or impact. It was postulated recently that the v-TAC conversion from venous blood could mitigate the acute changes in the arterial baseline induced by a transient change in breathing pattern 19. We, therefore, conducted a post hoc analysis of our data set to consider the potential effect of transient changes in breathing pattern.…”
Section: Introductionmentioning
confidence: 99%
“…Data are lacking on the prevalence or impact. It was postulated recently that the v-TAC conversion from venous blood could mitigate the acute changes in the arterial baseline induced by a transient change in breathing pattern 19. We, therefore, conducted a post hoc analysis of our data set to consider the potential effect of transient changes in breathing pattern.…”
Section: Introductionmentioning
confidence: 99%
“…The method evaluated further in this PhD project is the one by Rees et al (commercially called Roche v-TAC ™ , referred to as 'v-tac' in the dissertation) (43) which calculates arterial equivalents from peripheral venous blood and has been suggested for use in the ED (44,45) and pulmonary departments (46). This method employs physiology-based mathematical models, where it assumes good perfusion at the tissues, with little or no anaerobic metabolism across the tissue bed (details of the method are described in papers III and IV (3,4)). v-tac has been evaluated on acute patients (45,47), patients with COPD (44,48,49), respiratory failure (50) and those undergoing NIV treatment (47), and has been shown to function well within 2 standard deviations (SD) of ± 0.026 and ± 0.5 kPa for pH and PCO2 (48) when compared to measured arterial values; well within the limits of what Rang et al (37) reported as clinically acceptable.…”
Section: Alternative Methods To Assess Arterial Acid-base Statusmentioning
confidence: 99%